2010
DOI: 10.1111/j.1601-5037.2009.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of oral health knowledge, attitude and behaviour of non‐medical, para‐medical and medical students in Udaipur city, Rajasthan, India

Abstract: All the students showed low level of knowledge and the preventive behaviour among the students could still be improved. The results indicate that the knowledge was not enough to influence the oral health behaviour, but behaviour showed linear relationship with attitude of the students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
2
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 40 publications
4
34
2
8
Order By: Relevance
“…Singh et al [22] reported a linear positive relationship between oral health knowledge and behavior. Sharda and Shetty [23] and Braimoh and Owoturo [18] reported non-significant linear relationship between oral health behavior and knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Singh et al [22] reported a linear positive relationship between oral health knowledge and behavior. Sharda and Shetty [23] and Braimoh and Owoturo [18] reported non-significant linear relationship between oral health behavior and knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Of the medical students, 59.5% expressed a willingness to quit smoking, as did 54.2% of the non‐medical students (Chkhaidze et al ., ). Regarding oral health risk behavior in India, Sharda and Shetty () found significantly lower behavior scores for the non‐medical students than for the para‐medical and medical categories. In terms of sexual risk behavior, no difference in at least one sexual risk behavior between medical and non‐medical university students was found in Xinjiang, China (Maimaiti et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, health science or medical students seem to have greater knowledge of health behavior risk awareness. For example, in Pakistan, the knowledge score (healthy lifestyle and dietary habits) of medical students was better (with 94.7% of medical students scoring good > 17 vs 52%) than non‐medical students (Sajwani et al ., ); in China, medical students had higher smoking‐related knowledge than non‐medical students (Han et al ., 2011; 2012); and in India, health professional students reported significantly higher oral health scores than their comparison group (Kumar Tadakamadla et al ., ; Sharda & Shetty, ). Health risk behaviors may be influenced by a lack of awareness and low perceived health benefits (Steptoe & Wardle, ).…”
Section: Introductionmentioning
confidence: 99%
“…21 Sharda ve ark., sağlık eğitimi alan ve almayan üniversite öğrencileri üzerinde yaptıkları diş plağı ve zararları, diş eti kanamalarının nedenleri ve nasıl önlenebileceği gibi soruları içe-ren çalışmada, öğrencilerin %50'den azının bu konuda yetersiz bilgiye sahip oldukları sonucuna varmışlardır. 22 Çalışma sonuçlarımıza göre, periodontal hastalıkların sebepleri eğitim sonrasında hemşirelik öğrencileri tarafından daha iyi anlaşıl-mış, etkenlerle hastalık arasındaki ilişki kurulmuştur. Diş eti hastalıklarının belirtileri %50'den oldukça fazla sayıda öğrenci tarafından kavranmıştır ki; Kılınç ve ark.nın çalışmasındaki gibi, sağlık eğitimi veren okullarda bu farkındalığın, eğitim almamış öğrencilerden daha fazla olduğu görüşünü desteklemektedir.…”
Section: Discussionunclassified